Empat Kompetensi Guru dalam Mengembangkan Pembelajaran - Purwaningsih, Yeti (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
Until now, teachers are still striving to become an ideal teacher and the majority of teachers have not yet met the ideal teacher level when the benchmark used is teacher competency. This research aims to describe four teacher competencies that are carried out in order to develop learning. This research method is library research where in obtaining data you will use documentation techniques. The codified data is then analyzed using content analysis techniques. The results of this research show that teacher competence has an impact on the implementation of learning, namely four concepts starting from pedagogical competence with efforts to improve teacher abilities, personality competence with efforts to improve teacher attitudes and behavior for the better, social competence with efforts to establish good communication from teachers. to students and professional competence by increasing teachers' understanding of the material they teach.